USING A COMBINATION OF PERINDOPRIL, INDAPAMIDE AND ROSUVASTATIN IN THE TREATMENT OF PATIENTS WITH HYPERTENSION AND DYSLIPIDEMIA - O. M. Drapkina; A. S. Lishuta (Рациональная фармакотерапия в кардиологии)
Aim. To study the antihypertensive and hypolipidemic effect of a group of drugs including perindopril,rosuvastatin and fixed-dose combination of perindopril and indapamide, in ambulatory patients with hypertension and dyslipidemia.Material and methods. Analysis of the medical data of patients treated with perindopril, indapamide and rosuvastatin in the multicenter, non-interventional study (SYNERGY) was performed. Patients had a diagnosis of hypertension and dyslipidemia, determined in routine clinical practice. Therapy was prescribed to patients in various dosing regimens. The data of anamnesis, physical status, blood pressure measurements, lipid levels were taken from the patient's medical records. The safety assessment was also performed. The duration of follow-up was 8 weeks.Results. A total of 1383 patients were included into the analysis, 53.5% (n=740) of women and 46.5% (n=643) of men. The average age was 55.8 years. 914 patients (66.1%) had previously received antihypertensive therapy, and 439 (31.7%) had previously received lipid-lowering therapy. A significant reduction in the levels of systolic (SBP), diastolic BP (DBP), and low-density lipoprotein cholesterol (LDL-c) was found at the end of the study in all study groups (p<0.05). This demonstrated an adequate antihypertensive and lipid-lowering effect of all treatment regimens. The mean decrease in SBP in treatment groups ranged from 14.3 to 36.2 mm Hg; the mean decrease in DBP – from 3.3 to 22.2 mm Hg. The maximum decrease in SBP was found in the group of perindopril + indapamide + rosuvastatin (PIR) 8 + 2.5 + 20 mg (36.2±12.3 mm Hg); the maximum decrease in DBP – in the group of perindopril + rosuvastatin 8 + 10 mg. The mean decrease in LDL-c level due to the combined treatment with perindopril, indapamide and rosuvastatin ranged from 0.62 mmol/L in PIR groups 2 + 0.625 + 5 mg and 8 + 2.5 + 5 mg to 1.78 mmol/L in PIR group 8 + 2.5 + 20 mg. Three of 1,383 patients reported adverse events after 4 weeks of treatment, while 13 patients – at the end of the study.Conclusion. PIR therapy resulted in a significant reduction in blood pressure in all treatment groups compared with baseline levels. A dose-dependent reduction in SBP and LDL-c levels was found in all treatment groups. The tolerability of all treatment regimens was good.